GENDER EQUALITY IN THE WORKPLACE: STRATEGIES FOR CLOSING THE PAY GAP - Islomova Sevinch Botirjon qizi (Web of Journals Publishing, 2023)
This article addresses the persistent issue of the gender pay gap in the workplace and explores strategies aimed at closing this gap. Gender equality is not only a matter of social justice but a key driver of economic growth and organizational success. By examining the root causes of the pay gap, discussing policy measures, and highlighting best practices from companies that have successfully narrowed the gap, this study offers insights into how organizations and policymakers can work together to create fair, equitable, and inclusive work environments.
Keywords: Gender Equality, Gender Pay Gap, Workplace, Strategies, Policy Measures, Inclusion.